2018
DOI: 10.4315/0362-028x.jfp-17-380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Method for Rapid Detection of Listeria monocytogenes in Dry-Cured Ham Based on Impedanciometry Combined with Chromogenic Agar

Abstract: The food industry is in need of rapid, reliable methodologies for the detection of Listeria monocytogenes in ready-to-eat products, as an alternative to the International Organization of Standardization (ISO) 11290-1 reference method. The aim of this study was to evaluate impedanciometry combined with chromogenic agar culture for the detection of L. monocytogenes in dry-cured ham. The experimental setup consisted in assaying four strains of L. monocytogenes and two strains of Listeria innocua in pure culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…In a previous study carried out by our research group, an impedance measurement combined with OCLA to detect L. monocytogenes in dry-cured ham offered excellent values for RT, SP and SE (Labrador, Rota, Pérez, Herrera, & Bayarri, 2018), but the impedance measurement time was longer than in the present study (40 h vs 24 h).…”
Section: A N U S C R I P Tcontrasting
confidence: 58%
See 3 more Smart Citations
“…In a previous study carried out by our research group, an impedance measurement combined with OCLA to detect L. monocytogenes in dry-cured ham offered excellent values for RT, SP and SE (Labrador, Rota, Pérez, Herrera, & Bayarri, 2018), but the impedance measurement time was longer than in the present study (40 h vs 24 h).…”
Section: A N U S C R I P Tcontrasting
confidence: 58%
“…In a previous study carried out by our research group, the pathogen was subjected to stressful conditions before inoculation in dry-cured ham. The detection of L. monocytogenes was not influenced by previous stress (Labrador, Rota, Pérez, Herrera, & Bayarri, 2018). This demonstrated that preenrichment media allowed the recovery and multiplication of the pathogen.…”
Section: A N U S C R I P Tmentioning
confidence: 73%
See 2 more Smart Citations